Are Urban Vertebrates City Specialists, Artificial Habitat Exploiters, or Environmental Generalists?. (9th August 2018) - Ducatez, Simon; Sayol, Ferran; Sol, Daniel; Lefebvre, Louis
Abstract: Although urbanization is a major threat to biodiversity, some species are able to thrive in cities. This might be because they have specific adaptations to urban conditions, because they are able to cope with artificial habitats in general or because they are generalists that can live in a wide range of conditions. We use the latest version of the IUCN database to distinguish these possibilities in 25, 985 species of the four classes of terrestrial vertebrates with the help of phylogenetically controlled methods. We first compare species occurrence in cities with that of the five other artificial habitats recognized by the IUCN and use principal components analyses to ask which of these most resembles cities. We then test whether urban species have a wider habitat breadth than species occurring in other, non-urban, artificial habitats, as well as species that occur only in natural habitats. Our results suggest that the proportion of terrestrial vertebrates that occur in urban environments is small and that, among the species that do occur in cities, the great majority also occur in other artificial habitats. Our data also show that the presence of terrestrial vertebrates in urban habitats is skewed in favor of habitat generalists. In birds and mammals, species occurrence in urban areas is most similar to that of rural gardens, while in reptiles and amphibians, urban areas most resemble pasture and arable land. Our study suggests that cities are likely not unique, as is often thought, and may resemble other types of artificial environments, which urban exploiters can adapt to because of their wide habitat breadth.